Activation of RAW 264.7 cells by a polysaccharide isolated from Antarctic bacterium Pseudoaltermonas sp. S-5. (5th October 2015) - Li, Jing; Qian, Wen; Xu, Yanghui; Chen, Guochuang; Wang, Guodong; Nie, Songliu; Shen, Bingxiang; Zhao, Zhigang; Liu, Chunyan; Chen, Kaoshan
Highlights: Exopolysaccharide (PEP) activated RAW 264.7 cells in resting state. PEP activated NF-κB and p38 MAPK signaling pathways in RAW 264.7 cells. The two signaling pathways partially participated in PEP-activated RAW 264.7 cells. Abstract: The aim of this study was to examine the effect of extracellular polysaccharide (PEP) from Antarctic bacterium Pseudoaltermonas sp. S-5 on RAW 264.7 cells together with the underlying signaling pathways. Our results illustrated that PEP induced dendritic-like morphological change in RAW 264.7 cells, and increased the productions of nitric oxide (NO) and tumor necrosis factor-α (TNF-α). PEP could also enhance phagocytic activity of RAW 264.7 cells. Results of immunofluorescence staining and immunoblotting indicated that PEP caused the nuclear translocation of nuclear factor (NF)-κB subunit p65, the degradation of IκB-α and up-expression of phosphorylated p38 mitogen-activated protein kinase (MAPK) in RAW 264.7 cells. According to pharmacological evaluation with specific enzyme inhibitors, both NF-κB and p38 MAPK signaling pathways were involved in the generation of NO and TNF-α induced by PEP. All these results indicated that PEP from Antarctic bacterium Pseudoaltermonas sp. S-5 activated RAW 264.7 cells through NF-κB and p38 MAPK signaling pathways.